Readings in the applied economics of Africa : volume 1, micro-economics - Whetham, Edith Holt.; Currie, Jean I. (Cambridge : Cambridge University Press, 1967)
This study is designed to supplement courses in economics given in African universities. In this volume, the use of resources is considered from the angle of the firm of the farm. Parts 1 and 2 deal respectively with agriculture and with industry, and part 3 considers prices and markets, through which goods and services are exchanged and incomes are earned.
Includes bibliographical footnotes.
ne 08/11/2019
Loans
Keywords: Economic history; Africa, Sub-Saharan.